Resposta :
Resolução!
[tex] ( - \frac{1}{5} + \frac{3}{4} + 1) \times \frac{1}{3} = mmc =20 \\ \\ ( \frac{ - 4 + 15 + 20}{20} ) \times \frac{1}{3} \\ \\ \frac{31}{20} \times \frac{1}{3} = \frac{31}{60} \\ \\ \\ espero \: ter \: ajudado[/tex]

Resposta:
[tex] \frac{31}{60} [/tex]
Explicação passo-a-passo:
[tex]( - \frac{1}{5} + \frac{3}{4} + 1) \times \frac{1}{3} = mmc = 20[/tex]
[tex]( \frac{ - 4 + 15 + 20}{20} ) \times \frac{1}{3} = \frac{31}{20} \times \frac{1}{3} = \frac{31 \times 1}{20 \times 3} = \frac{31}{60} [/tex]